Perfect match eaudiobook - Picoult, Jodi (2013)
Jodi Picoult is a #1 New York Times bestselling author whose books have been adapted for both the small and silver screen. In Perfect Match, she spins a story of a mother who does the unthinkable to protect her child. Lines blur when assistant DA Nina Frost learns that her five-year-old son Nathaniel was sexually abused by a priest. She takes the law into her own hands, killing the man accused. But then details surface clearing the priest and putting Nina's future in jeopardy.